Boosting Performance at Machmudah Cooking Spices: Unveiling the Impact of Motivation and Compensation - Satunggale Kurniawan; Muhammad Afifi (International Journal of Management Science, 2024)
Human Resources (HR) is an important asset in supporting motivation to achieve success in an organisation. HR is the implementer of all organisational policies and therefore needs to be equipped with adequate knowledge. The importance of human resources needs to be recognised by all levels of management in MSMEs. Micro, small and medium enterprises are the main actors of economic activities in Indonesia. The future of development lies in the ability of micro, small and medium enterprises to develop independently, therefore this research focuses on the influence of work motivation and compensation on employee work performance in Machmudah Cooking MSMEs. This research design uses a quantitative research approach and has the result that work motivation and compensation simultaneously have a significant effect on employee work performance at Bumbu Masak Machmudah (BMM). This means that the more work motivation and compensation increase, the more work performance will increase.